Pengaruh Manajemen Talenta dan Manajemen Pengetahuan Terhadap Efektivitas Organisasi dan Kinerja Organisasi - Ninik Indrayani; Toni Herlambang; Ni Nyoman Putu Martini (RELASI : JURNAL EKONOMI, 2023)
This study aims to examine the effect of talent management and knowledge management on organizational effectiveness through organizational performance. This research was conducted in April – May 2022. The number of respondents was 100 people. The sampling technique used a questionnaire. The results showed that there was a positive and significant influence of talent management on the organizational performance of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of knowledge management on the organizational performance of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of talent management on the organizational effectiveness of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of knowledge management on the organizational effectiveness of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant effect of organizational performance on the organizational effectiveness of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of talent management on organizational effectiveness through the organizational performance of the Fatimah Islamic Hospital in Banyuwangi. There is a positive and significant influence of knowledge management on organizational effectiveness through the organizational performance of the Fatimah Islamic Hospital in Banyuwangi.